Exploring Identity Shifts in Individuals Undergoing Long-Term Psychodynamic Therapy - Schneider, Lukas; Karna, Wioleta (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to explore the lived experiences of individuals undergoing long-term psychodynamic therapy. This qualitative research employed a phenomenological design to gain an in-depth understanding of identity transformation in therapy. Data were collected through semi-structured interviews with 24 participants from Germany, all of whom had been engaged in psychodynamic therapy for at least two years. Participants were recruited through therapy clinics and online mental health platforms using purposive sampling. The interviews, lasting between 60 to 90 minutes, were transcribed verbatim and analyzed thematically using NVivo software. The process of theoretical saturation was achieved after the 24th interview, and data analysis involved iterative coding and theme development guided by constant comparison. Analysis revealed five major themes reflecting the participants’ experiences of identity shifts: Emerging Self-Awareness, Transformation of Relational Patterns, Integration of Past and Present, Emotional Regulation and Expression, and Therapeutic Relationship as Catalyst. Subthemes included recognition of inner conflicts, emotional insight, boundary setting, reframing childhood, managing emotional outbursts, and relational learning. Participants described a growing sense of coherence, self-continuity, and emotional resilience as therapy progressed. They attributed these changes to the reflective, safe, and relationally rich environment of long-term psychodynamic therapy, where insight, emotional processing, and narrative reconstruction facilitated profound identity development. The findings suggest that long-term psychodynamic therapy supports multidimensional identity transformation by fostering emotional awareness, relational restructuring, narrative integration, and self-reflection. The therapeutic relationship plays a pivotal role as both a mirror and catalyst for these changes. These insights underscore the value of sustained psychodynamic work in addressing complex identity issues and highlight its relevance for individuals with developmental and relational trauma histories.